KETERASINGAN DALAM PENGALAMAN PASIEN COVID-19 TINJAUAN MENURUT RELASIONALITAS ARMADA RIYANTO - Meidinata, Marianus Ivo; Setiawan, Charles Virgenius (STIPAS Keuskupan Agung Kupang, 2021)
In this study, the authors focus on the feeling of alienation experienced by covid-19 patients. Feeling alienated is something that pops up when they do the part. The methodology in this study takes a qualitative approach. The author tries to see the sense of alienation from a philosophical point of view; and how they deal with that sense of alienation. The author conducted in-depth interviews with several covid-19 survivors, complemented them with literature studies, and tried this phenomenon through the philosophy of relationality of Armada Riyanto, with a phenomenological approach. This study reveals the feeling of alienation experienced by covid-19 patients. This sense of alienation arises due to three factors, namely loneliness and loneliness, negative stigma on covid-19 patients, and their inability to express themselves. This study confirms that the relationship is a necessity. The nature of human existence is to be present together with others. In the context of this separation, relational (which is often considered to be lacking in quality) turns out to be a means of missing presence.